Os malefícios da corrupção política na concretização do estado democrático de direito angolano - Miguel, Adérito Pilartes Henrique (2016)
Corruption is a space where the power of addiction in the public interest, is binding on private interests, which his action challenging the ultimate purposes of the democratic state and law. The methodology used was a qualitative method using the bibliography, in which recourse to query location and activity of diverse sources of information written for the collection of general and specific data. In our work we come to the conclusion that we can not eliminate corruption so that we can achieve the ultimate goal of a democratic state of law, but we can reduce it, through a continuous process improvements and ongoing legal and cultural institutions, which view tackle its causes and effects.